Fairness in the presence of semi-rational parties in rational two-party secure computation. (1st January 2013) - Sun, Zhonghong
Reputation is commonly used in game theory for mutual cooperation. Assuming that parties value their reputation as well as their payoffs just like people in the real world, this paper considers reputation assumptions when defining the utilities. The new utility consists of two parts: the reputation part and payoff part. The parties are redefined according to the new utility definition. Besides, to represent a more realistic adversary model, a new adversary named semi-rational party is proposed. The semi-rational parties behave like the combination of rational and covert parties. At last, a rational two-party secure computation protocol is constructed. The proof of fairness in the presence of the semi-rational party is stressed in this paper.